Analisis Sistem Pembelajaran Boarding School Pada Jenjang Perguruan Tinggi Keagamaan Buddha (Studi Kasus Di Stab Kertarajasa Malang Dan Stab Maha Prajna Jakarta) - Agustina Sri Rahayu; Jeny Harianto; Sutrisno (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
This research aims to know and to analyze the boarding school learning system applied at STAB Maha Prajna Cilincing and STAB Kertarajasa Malang. This research uses qualitative research methods and the results of the study are delivered descriptively with purposive sampling taken to the STAB leaders, lecturers, boarding carers, dormitories and students. Based on the results of the analysis shows that STAB Kertarajasa approached the ideal in the applied boarding school system compared to STAB Maha Prajna because the boarding school participants at STAB Kertarajasa were all Samanera and Atthasilani and the boarding school learning system at STAB Kertarajasa was considered more ideal and almost referring to education in the past, namely education at Nalanda University.